El diálogo posible entre dos tradiciones. Entre la “escucha del otro” y el “principio de caridad” - Monteagudo, Cecilia (2013)
In the framework of the discussions produced after the fiftieth anniversary of Hans-Georg Gadamer’s publication of Truth and Method (1960) this paper intends to address two issues of Gadamer’shermeneutics. The first issue seeks to establish the articulating thread betweenTruth and Method, still attached to the debate with traditional hermeneutics, and some formulations of Gadamer’s later work, where “the soul of hermeneutics” isdisplayed as “art of listening to the other”. The second issue seeks to highlight the rehabilitation that Gadamer makes of the Socratic-Platonic eumeneîs élenchoi, an expression that he translates as the “art of strengthening the discourse of theother”, whose explicitness in his later work has enabled many interpreters of his work to see a possible dialogue between his hermeneutics and some aspects ofthe philosophy of Donald Davidson.